The components of Muslim society in the Makki Suwar: al-Isrā’ Surah as a model - Keles, Kubra; Al-Zyout, Abdallah (Dirasat: Human and Social Sciences, 2020)
The purpose of this study is to uncover the Muslim society elements in al-Isrā’ Surah al-makki. It introduces the definition of the society, its factors and the way the al-Isrā’ Surah includes these components in its verses. The research uses the inductive method, descriptive method and the analytical method. The reason for choosing al-Isrā’ Surah is that it’s the last surah was revealed in the Makki era and so paved the way for the Madeni era. al-Isrā’ Surah also has a comprehensive topics in creed, individual and collective rules of conduct. The results demonstrate that al-Isrā’ Surah included the elements that form the society as the human, the environment, and the relations in its verses.